SOSIALISASI MENINGKATKAN KESADARAN PEKERJA MIGRAN: HAK, PERLINDUNGAN, DAN KEWAJIBAN BAGI ORANG TUA SISWA DI SEKOLAH INDONESIA KUALA LUMPUR - Fakultas Hukum Universitas Negeri Surabaya; Vita Mahardhika; Arinto Nugroho; Muh. Ali Masnun; Pudji Astuti; Dita Perwitasari (Fakultas Hukum, Universitas Negeri Surabaya, 2025)
This community service program aims to enhance the awareness and understanding of Indonesian migrant worker parents whose children are enrolled at the Indonesian School of Kuala Lumpur (SIKL) regarding their rights, available legal protections, and parental responsibilities in supporting their children's education abroad. The primary issue identified is the limited legal literacy among migrant workers, particularly related to mechanisms of protection, assistance, and their obligations in ensuring a conducive educational environment for their children. The program was carried out through several stages, including coordination with the school, preparation of educational materials, administration of a pre-test, delivery of the socialization session through presentations and interactive discussions, and a post-test to measure comprehension improvement. The results indicate a significant increase in participants’ understanding of migrant workers’ rights, legal protections, and their responsibilities as parents. This improvement is demonstrably reflected in the comparison between pre-test and post-test outcomes. Participants also expressed positive responses and encouraged the continuation of similar programs in the future. This PKM initiative is expected to contribute to strengthening legal literacy among Indonesian migrant workers and to reinforcing parental roles in supporting the academic success of their children overseas.